An alpha particle detector based on a GPS mosaic scintillator plate for continuous air monitoring in plutonium handling facilities. (October 2016) - Kaneko, Junichi H.; Izaki, Kenji; Toui, Kouhei; Shimaoka, Takehiro; Morishita, Yuki; Tsubota, Youichi; Higuchi, Mikio
Abstract: An alpha particle detector was developed for continuous air monitoring of radioactive contamination in working chambers at plutonium handling facilities. A 5-cm-square Gd2 Si2 O7 :Ce (cerium-doped gadolinium pyro-silicate, GPS:Ce) mosaic scintillator plate for alpha particle measurements was fabricated from GPS single-crystal grains of around 550 μm diameter; the GPS grains were made of a GPS polycrystalline body grown using a top seeded solution method. The scintillator layer thickness was approximately 100 μm. The surface filling rate of the GPS grains was ca. 62%. To suppress the influence of non-uniformity of pulse heights of a photomultiplier tube, a central part of ∅ 40 mm of a 76-mm-diameter photomultiplier tube was used. In addition, 3 mm thick high-transmission glass was used as a substrate of the scintillator plate. The detector achieved energy resolution of 13% for 5.5 MeV alpha particles, detection efficiency of 61% and a radon progeny nuclide reduction ratio of 64.5%. A new alpha particle detector was developed to achieve a high radon progeny nuclide reduction ratio approaching that of a silicon semiconductor detector, with high resistance to electromagnetic noise and corrosion. Highlights: An alpha particle detector was developed for continuous air monitoring. The detector comprises a mosaic scintillator plate and a photomultiplier tube. A 5-cm-square GPS mosaic scintillator plate was fabricated. Its respective energy resolution and detection efficiency were 13 and 61%. The radon progeny nuclide reduction ratio of the developed detector was 64.5%.